Permission for municipalities to establish and finance prizes and awards for athletes in electronic sports (Ius Novum, 2024)
The article, original in nature, was devoted to the issue of awards and prizes for e-sports players. The motivational financial instruments in question are regulated in the Sports Law, specifically in Article 31. The author has attempted to solve the legal problem of finding an answer to the question of the legal possibility for municipalities to establish and finance prizes and awards for e-sports players under Article 31 of the Sports Law. Due to the singular and causal works in the field of e-sports funding, which do not address the issue of establishing and funding prizes and awards for e-sports players under Article 31 of the Sports Act, the elaboration of this issue within the framework of the article will, in the author’s opinion, undoubtedly enrich the current literature on the subject. The introductory considerations focus on presenting the essence of the definition of sport and attempt to qualify e-sports as a sport under the Sports Act, which is significant for the possibility of local authorities establishing prizes and awards. The key views of the literature, judicial decisions, and the state of the law in this area were presented. Investigations in this area have led to the conclusion that, with a few reservations, it is possible to qualify e-sport as a sport. Subsequently, the focus was on the legal aspects concerning the possibility for municipalities to establish and finance prizes and awards for e-sports players. The problemconcerning the understanding of competition under the Sports Act was resolved, and it was pointed out that e-sports players, despite the lack of a Polish e-sports association, can participate in sports competitions under the Sports Act. In addition, the problematic premise concerning the importance of a given sport for a local authority has been clarified. The final considerations in this area have allowed de lege ferenda postulates to be formulated. The analysis is based on legal norms and statements of doctrine and jurisprudence. The article contains considerations concerning the normative and dogmatic sphere as well as the sphere of law application by administrative courts. The research has a national character. In this article, the dogmatic-legal method has been applied, consisting of the analysis of legal regulations on the establishment and financing of awards and prizes for players of electronic sports. The subject matter discussed is divided into several main editorial units. The different parts correspond to the main outline of the problem and its relation to important scientific and practical issues.